Supply chain flexibility and SMEs internationalization: A conceptual framework - Sylvia Mercedes Novillo Villegas; Hans-Dietrich Haasis (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
This paper has the aim of analyzing the relationship of logistics capabilities and supply chain flexibility (SCF) as part of small and medium-sized enterprises (SMEs) internationalization strategy through a review of relevant research in these areas. This review will constitute the foundation for developing an integrative conceptual framework to understand the relationship. An integrative literature review in internationalization approaches, SCF and logistics capabilities from 2006 through 2016 was conducted. The analysis of an extract from this literature review is presented to identify the key elements that contribute to the SMEs' flexibility as a strategy to achieve their internationalization goals. The role that logistics capabilities play in achieving SCF as part of SMEs internationalization strategies has not been analyzed in literature from an integrative conceptual perspective. Further, the areas of research were conducted mostly in large firms from developed markets. A multi-disciplinary approach is used in this research to address this gap. As such, this paper is the first on analyzing the relationship between the areas of interest. This constitutes the initial phase of building a theory on the relationship between SMEs internationalization, SCF, and logistics capabilities. Further research will be necessary to empirically test the conceptualized relationships in both developed and emerging markets. This paper also presents managerial implications. The relationships between the presented areas contribute to a better understanding of the influence of logistic capabilities regarding SMEs flexibility in a supply chain context. This will lead to improving the SMEs' innovation and logistics management while designing internationalization strategies.
urn:nbn:de:gbv:830-88217673; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; maritime security; illicit trade; detection architecture; discrete event simulation